Planejamento do portfólio de produtos : uma abordagem a partir da compreensão da experiência de escolha do usuário frente à diversidade de alternativas - Assis, Maria Valéria Gonçalves de (Universidade do Vale do Rio dos Sinos, 2013)
Choice overload is an effect related to great variety of options in user's choice experience. Other research efforts have shown that, when the number of options is increased, there occur adverse consequences to choice experience, such as decreased pleasure and decreased satisfaction. Based on the direct sale market for hygiene and beauty products, our aim was to understand user choice experience in relation to diversity of product alternatives for the shampoo, conditioner and liquid soap segments. Two experiments were conducted to understand user experience: in the first one (n = 103), the amount of products was manipulated through different colors; in the second one (n = 96), the amount was manipulated using different types of packaging. A survey (n = 101) was also applied to understand some habits and consumer preferences for hygiene and beauty products. As a result, it was found the opposite of other research efforts on choice overload: users support the amount of options (50% above the market average) and have a preference for specific products for their use. The results obtained on the consumer choice experience for the hygiene and beauty segment provide a basis for planning of product portfolios on this segment, a strategic product-system element of a company from the strategic design perspective. Planning the product portfolio based on user's choice experience helps creating a positive shopping experience for consumer and benefits the producer.
Keywords: Sobrecarga de escolha; Portfólio de produtos; Design estratégico; Choice overload; Product portfolio; Strategic design; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial